A study of network characteristics in diffusion-based molecular communication - Adeebah Jamar, 1989- , author; Nurul Mu'azzah Abdul Latiff, supervisor; Fakulti Kejuruteraan Elektrik (2015)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2015